Can group rights justify the denial of education to children? The Amish in the United States as a case study - Cohen-Almagor, Raphael (SN Social Sciences, 2021)
Multiculturalism gives preference to group rights over individual rights. This may challenge democratic values. This paper focuses on the Amish denial of education from their adolescents. Criticizing Wisconsin v. Yoder (Wisconsin v. Yoder 406 U.S. 205 (1972)), the paper analyses the power of the Amish community over its members. The main questions are: Is it reasonable to deny the Amish adolescents’ standard American education? What are the limits of state interference in norms of illiberal communities who invoke separatism as a mechanism of cultural and religious preservation?
Received: 16 December 2020 / Accepted: 13 April 2021; ORIGINAL PAPER
Keywords: Amish; Education; Open future; State interference; Wisconsin v. Yoder